LEGAL PROTECTION OF PATIENT RIGHTS AND LEGAL RESPONSIBILITIES OF MEDICAL PERSONNEL IN HEALTHCARE SERVICES IN INDONESIA - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (Adisam Publisher, 2025)
This study discusses legal protection of patients' rights and the legal responsibilities of medical personnel in health services in Indonesia. Patients' rights as recipients of health services are fundamental rights that must be protected through various regulations such as Law No. 36 of 2009 concerning Health and Law No. 44 of 2009 concerning Hospitals, which guarantee the rights to information, privacy, and service safety. On the other hand, medical personnel have legal responsibilities that include criminal, civil, and administrative responsibilities to ensure safe, professional, and standard-compliant services. This study uses a literature review method with an analysis of relevant laws, legal literature, and court decisions. The results of the study show that although a legal framework is in place, there are still challenges in implementing patient rights protection and enforcing the legal responsibilities of medical personnel, particularly in relation to understanding rights and obligations, access to justice, and complaint mechanisms. Strengthening regulations, education, and mechanisms for supervision and dispute resolution are essential to improve the quality of equitable health services in Indonesia.